Socio-economic assessment in environmental impact assessment: experience and challenges in Lithuania - Dagiliūtė, Renata; Juozapaitienė, Gintarė (Journal of Environmental Engineering and Landscape Management, 2015)
In 2011, the Environmental Impact Assessment (EIA) Law amendment was approved and a socio-economic assessment formally became an integrated part of EIA in Lithuania. Therefore, this study examines a socio-economic assessment in the environmental impact statements (EIS) and the perceptions of the EIA experts towards a socio economic assessment. Although formally a socio-economic assessment has been validated only recently, 30% of specialists claimed having conducted a socio-economic assessment in detail prior to the amendments to the law. Thus, the EIS analysis has shown a rather poor consideration of these issues as mainly creation of work places was addressed. The survey has shown that preparation of the EIA documents after the formalisation of a socio-economic assessment would change mainly nominally. The EIA experts working in the private sector were more optimistic than those from state institutions. Reluctance of changes and personal attitudes have to be addressed, especially those particular to the experts of state institutions. In addition, methodological guidance, integrative approach and public involvement into the decision-making process could change the current situation and increase the effectiveness of the EIA process and the social impact assessment in general.